Answer:
No solutions
Step-by-step explanation:
[tex]y''+4y'+4y=0,\:y(0)=1,\:y'(0)=1\\\\m^2+4m+4=0\\\\(m+2)(m+2)=0\\\\m=-2[/tex]
Thus, since we have equal real roots, we use the general solution [tex]y(x)=C_1e^{m_1x}+C_2e^{m_1x}[/tex] and our initial conditions to set up our system of equations:
[tex]y(x)=C_1e^{-2x}+C_2e^{-2x}\\\\y(0)=C_1e^{-2(0)}+C_2e^{-2(0)}\\\\1=C_1+C_2[/tex] <-- First one
[tex]y(x)=C_1e^{-2x}+C_2e^{-2x}\\\\y'(x)=-2C_1e^{-2x}-2C_2e^{-2x}\\\\y'(0)=-2C_1e^{-2(0)}-2C_2e^{-2(0)}\\\\1=-2C_1-2C_2[/tex] <-- Second one
Solve the system
[tex]C_1+C_2=-2C_1-2C_2\\\\3C_1+3C_2=0\\\\3C_1=-3C_2\\\\C_1=-C_2[/tex]
[tex]1=C_1+C_2\\\\1=-C_2+C_2\\\\1=0[/tex]
Therefore, there are no solutions to the differential equation given the initial conditions.